2018
DOI: 10.1021/acs.est.8b04707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Library Composition on SourceTracker Predictions for Community-Based Microbial Source Tracking

Abstract: Community-based microbial source tracking (MST) utilizes high-throughput DNA sequencing to profile and compare the microbial communities in different fecal sources and environmental samples. SourceTracker, a program that compares a library of OTUs from fecal sources (i.e., sources) to those in environmental samples (i.e., sinks) in order to determine sources of fecal contamination, is an emerging tool for community-based MST studies. In this study, we investigated the ability of SourceTracker to determine sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Common MST methods use specific bacterial primers from hosts to measure quantities via quantitative real-time PCR (qPCR) (Brown et al, 2017; Harwood et al, 2014). However, the development of primers for fecal sources of interest may be time consuming and previous research has shown potential issues with specificity and sensitivity of qPCR (Brown et al, 2019; Green et al, 2014; Stewart et al, 2013). The usage of NGS methods to define the microbial community of aquatic and fecal samples using amplicon sequence variant (ASV), which can resolve the difference of sequences to a single nucleotide, increases the power of determining potential fecal contamination sources (Callahan et al, 2017; Unno et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Common MST methods use specific bacterial primers from hosts to measure quantities via quantitative real-time PCR (qPCR) (Brown et al, 2017; Harwood et al, 2014). However, the development of primers for fecal sources of interest may be time consuming and previous research has shown potential issues with specificity and sensitivity of qPCR (Brown et al, 2019; Green et al, 2014; Stewart et al, 2013). The usage of NGS methods to define the microbial community of aquatic and fecal samples using amplicon sequence variant (ASV), which can resolve the difference of sequences to a single nucleotide, increases the power of determining potential fecal contamination sources (Callahan et al, 2017; Unno et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…human, farm animal, bird, to determine sources of fecal contamination in the environment. The most common MST method uses quantitative real-time polymerase chain reaction (qPCR) and primers that target the 16S rRNA genes of host associated bacteria (Brown et al, 2017; Harwood et al, 2014), however, qPCR may suffer from specificity and sensitivity issues (Brown et al, 2019; Green et al, 2014; Stewart et al, 2013). In the last decade, advancements in high-throughput DNA sequencing has led to large-scale microbial community studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate how RAD may perform in real-world experiments, RAD was applied to an experiment by Brown et al [ 17 ], which simulated wastewater by spiking lake water samples with bacteria from sewage effluent or fecal samples. We considered the scenario where the sources of interest are lake water, sewage effluent, cow fecal matter, and horse fecal matter.…”
Section: Fecal Source Tracking Applicationmentioning
confidence: 99%